Novel imino- and aryl-sulfonate based photoacid generators for the cationic ring-opening polymerization of ε-caprolactone. Issue 28 (5th July 2021) - Lopez de Pariza, Xabier; Cordero Jara, Erick; Zivic, Nicolas; Ruipérez, Fernando; Long, Timothy E.; Sardon, Haritz
Abstract : The use of photoacid generators for the ring opening polymerization of cyclic esters is investigated. Abstract : Photoinduced polymerization is a useful tool in many industrial applications such as coatings, adhesives and 3D printing. However, the use of light to promote polymerization has been almost exclusively used for radical photopolymerization, thus excluding a wide variety of monomers. In this context, the use of light irradiation to trigger other polymerizations to produce degradable polymers has scarcely been studied. Herein, we investigate the use of six novel photoacid generators based on anthrone and anthraquinone chromophores capable of producing triflic, para -toluensulfonic and methanesulfonic acids upon 365 nm LED light irradiation to trigger the ROP of cyclic esters. The efficiency of the catalyst is shown to be strongly related to the chromophore and the sulfonate substituent. After characterizing the photodissociation process using UV-Visible and NMR spectroscopy, DFT calculations were carried out in order to understand the photodissociation mechanism. Their use as effective catalysts for the cationic ring-opening polymerization of ε-Cl is confirmed by 1 H NMR and SEC analysis either in solution or in bulk, obtaining fast polymerization rates at 100 °C. This catalyst family shows the ability to form polyester based coatings using light, expanding the number of coatings that may be prepared by photopolymerization processes.